2022
DOI: 10.3389/fmicb.2022.922760
|View full text |Cite
|
Sign up to set email alerts
|

Metabolites From Trypanosome-Infected Cattle as Sensitive Biomarkers for Animal Trypanosomosis

Abstract: Trypanosomes are important global livestock and human pathogens of public health importance. Elucidating the chemical mechanisms of trypanosome-relevant host interactions can enhance the design and development of a novel, next-generation trypanosomosis diagnostics. However, it is unknown how trypanosome infection affects livestock volatile odors. Here, we show that Trypanosoma congolense and Trypanosoma vivax infections induced dihydro-β- ionone and junenol, while abundance of dihydro-α-ionone, phenolics, p-cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 62 publications
0
17
0
Order By: Relevance
“…The low percentage of the camels identified with active infection might be due to the low sensitivity of the microscopic technique (Mossaad et al 2017;Njiru et al 2005, Getahun et al 2022. However, the molecular data showed that a significant number of camels were infected by trypanosomes, indicating that they might have subclinical infections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The low percentage of the camels identified with active infection might be due to the low sensitivity of the microscopic technique (Mossaad et al 2017;Njiru et al 2005, Getahun et al 2022. However, the molecular data showed that a significant number of camels were infected by trypanosomes, indicating that they might have subclinical infections.…”
Section: Discussionmentioning
confidence: 99%
“…Trypanozoon infection affected the PCV values significantly; camels that had active Trypanozoon infection were anaemic with the mean PCV value of 24.64 ± 6; however, microscopically negative camels had a higher PCV value of 30.14 ± 6, independent t-test, t = 3.303, P = 0.002, n = 222). Surra-infected camels were considerably anemic, an indication of trypanosomosis severity (Getahun et al 2022). Camels that were haemorrhagic, one infected with T. vivax (PCV 9%) and another with T. evansi type A (PCV 11%), were both severely anemic.…”
Section: Anaemia Associated With Trypanozoon Infectionmentioning
confidence: 99%
“…Livestock-Stomoxys interaction experiment demonstrated that livestock colors are not essential for the assessment of host but can be attracted to combinations of cues obtained from host such as visual and semio-chemicals. From our previous study we did not find semio-chemical differences between cattle of various colors, such as in their urine, dung, and breath odor profile [21] [43].…”
Section: Discussionmentioning
confidence: 99%
“…Trypanosomiasis is a vector-borne haemoparasitic disease of vertebrate animals caused by blood parasites belonging to the genus Trypanosoma (Mishra et al, 2017;Igbokwe, 2018). Trypanosomes are transmitted biologically by tsetse ies of the genus Glosina and mechanically by biting ies of the genus Tabanus and Stomoxys (Khan et al, 2018;Getahun et al, 2022). All species of vertebrates (domestic animals, wildlife, and humans) are susceptible to at least one species of trypanosomes (Oie 2021;Aliyu et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The major pathogenic species in domestic livestock are Trypanosoma congolense, T. vivax, T. brucei, and T. evansi for ruminants, T. simiae for pigs, T. evansi and T. equipadium for horses and donkeys (Khan et al, 2018;Oie 2021). In susceptible hosts, economic losses involve high morbidity and mortality, infertility and abortion (Getahun et al, 2022) and clinical signs include anorexia, anaemia, emaciation, profuse salivation, organ in ammation and damage, tissue degeneration, and necrosis (Igbokwe, 2018).…”
Section: Introductionmentioning
confidence: 99%